If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5(-6b + -8) + 2 = -278 Reorder the terms: 5(-8 + -6b) + 2 = -278 (-8 * 5 + -6b * 5) + 2 = -278 (-40 + -30b) + 2 = -278 Reorder the terms: -40 + 2 + -30b = -278 Combine like terms: -40 + 2 = -38 -38 + -30b = -278 Solving -38 + -30b = -278 Solving for variable 'b'. Move all terms containing b to the left, all other terms to the right. Add '38' to each side of the equation. -38 + 38 + -30b = -278 + 38 Combine like terms: -38 + 38 = 0 0 + -30b = -278 + 38 -30b = -278 + 38 Combine like terms: -278 + 38 = -240 -30b = -240 Divide each side by '-30'. b = 8 Simplifying b = 8
| 10*2.5-4(2.5+2)+3x=5(3-x) | | 8x-3=91 | | y-2=-2(x+2) | | 7b+7c= | | 8x=5x+45 | | 6j-5j=j | | 40x-5y=20 | | 6-2(x+4)=16 | | c(x)=800x+30000 | | y-1=13/9(x-3) | | 10*2.5-4(2.5+2)+3x=(3-x) | | 5a+1=2a+46 | | 9=2(n+7) | | 2+6z=6z | | 13/9(x-3) | | 35x^2+19x*8=6 | | 6(g-6)=2 | | 0.03x-0.05(x+2)=-0.08 | | 8-2m=14 | | 2cos^2+3sin^2x=0 | | 2y+2z+y+z=216 | | 7=6(u+3) | | K(k-4)=0 | | 5x-2x=90 | | 13=3u+8 | | 10+2.5-4(2.5+2)+3x=(3-x) | | 17.1=-4.8 | | 17=100(14/365)x | | (7+-1x)(6+x)=0 | | 10y-4(2.5+2)+3x=(3-x) | | 4x^2+3x-9=12 | | 6x-6-4x-28=-4 |